Unemployment Benefits Versus Conditional Negative Income Taxes - Snower, Dennis (IMF Working Papers; Working Paper ;, 1995)
The paper analyzes the wage-employment effects of replacing unemployment benefits by negative income taxes. It first surveys the major equity and efficiency effects of unemployment benefits versus negative income taxes, and summarizes the salient features of many European unemployment benefit systems in this light. Second, it presents a simple theoretical model that focuses on the relative wage-employment effects of unemployment benefits versus negative income taxes. Finally, it provides some empirical groundwork for assessing this relative effect.